Polybrominated Diphenyl Ethers in Human Milk in Taiwan - Horng, Chi-Ting; Chao, How-Ran; Chang, Chen-Min; Agoramoorthy, Govindasamy; Tzeng, Thing-Fong; Shieh , Po-Chuen (Asian Journal of Chemistry, 2010)
Several studies have linked polybrominated diphenyl ethers (PBDEs) to adverse biological effects in animals, giving rise to concerns that low-level exposure might cause similar effects in human beings as well. This study measured PBDE levels in breast milk samples from Pingtung, Taiwan. Study participants were healthy women recruited from Pingtung between April and October, 2007. Seven congener levels of PBDEs (BDE-47, 49, 99, 126, 153, 191, 209) in 20 breast milk samples were measured by a gas chromatography with a high resolution mass spectrometer (GC/Ms). The mean level of PBDEs in breast milk was 2650 ± 2580 pg/g lipid. The highest spearman correlation coefficient was found to be 0.893 (p < 0.001) between BDE-47 and BDE-99 in breast milk. The milk PBDE level was higher in women with the long menstrual cycle length (longer than 40 days versus less than 40 days; p = 0.004). Women with education level lower than high school had the significantly higher magnitude of BDE-99 compared to women with the higher education level (p = 0.032). Body burden of BDE-153 in women was increased with the increased head circumference of their offspring (r = 0.458, p = 0.042). Owing to few environmental monitoring and epidemio-logical data of PBDEs, this study encourages more longitudinal data from Taiwan to better understand the impact of PBDEs to human health in the industrialized small island of Taiwan.